THE ROLE OF PEER INFLUENCE IN SPORT SELECTION DECISIONS AMONG STUDENT-ATHLETES OF THE UNIVERSITY OF BENIN - RAPHAEL F. ANI; SHALLOM OZIOMA UKEJE (International Studies Journal)
Peer groups are central to student life as they play a significant role in the overall development of students, as they can be influenced towards activities that they might not have chosen. This pressure can be explicit, like direct encouragement or implicit with a feeling of the need to conform to group activities. While this can lead to positive outcomes, like joining a team sport for physical activity and social interaction, it can also result in choosing sports for popularity or acceptance rather than genuine interest. While previous research has shed light on various factors impacting sports choices, the specific role of peer groups in the context remains understudied. It is against this background that this study was carried out to investigate the role of peer influence in sport selection decisions among student-athletes of the University of Benin. Four research questions were raised and four corresponding hypothesis were formulated and tested at 0.05 level of significance. The study adopted a correlational survey design. The population of the study consisted of 140 student-athletes in the University of Benin. The sample size of the study comprised of 70 student-athletes.  Instrument used for data collection was a questionnaire. The data collected were analysed using descriptive statistics, while the t-test inferential statistics was used to test the hypotheses. The findings of the study revealed the following: There was a significant difference in how much peers' opinions influence sports selection between them. When it comes to social network influence, there was no statistical significance, suggesting that social network influence on sports choice does not differ significantly between the groups. This suggests that some student-athletes perceive a greater difference in sports preferences as a result of peer group diversity. The study concludes that peer influence is a critical determinant in the sport selection process, with implications for fostering inclusive and diverse participation in university sports. It was recommended that sports administrators and university educators should foster awareness among students about the impact of peer influence on their sports participation decisions.